A Case Study of Differentiated Instruction at Elementary School - Siti Aminuriyah; Ali Imron Al Ma'ruf; Anatri Destya; Minsih Minsih (AL-ISHLAH: Jurnal Pendidikan, 2023)
The objective of this research is to determine whether there is improvement in learning through the use of product differentiation learning. The research was carried out at a private elementary school in Surakarta during the academic year 2022/2023. This is a sekolah penggerak that utilises varied learning methods. Starting in the 2022/2023 academic year, the practice of differentiated learning will be introduced in grades 1 and 4. This study employs a qualitative research approach, specifically utilising a case study methodology. The data in this study consisted of documentation, field notes obtained through direct participant observation, and excerpts from interviews. Interviews were carried out with school principals, instructors in first and fourth grades, and students in first and fourth grades. The Simultaneous Inductive analysis technique was employed to analyse the data, which involved three distinct stages: data reduction, data reading, and data interpretation. The findings of this study suggest that the implementation of differentiated instruction, in conjunction with a thorough comprehension of differentiated learning by the teacher, can effectively yield the intended positive learning outcomes. The learning conducted caters to the diverse learning demands of every students, encompassing their readiness, profiles, and interests. The use of differentiated learning has yielded positive outcomes, as evidenced by increased student enthusiasm, active participation, and enhanced innovation in every session. Success indicators are evident in the process and learning outcomes. Students exhibit a sense of ease in their learning experience, while demonstrating growth in both hard and soft skills. Additionally, students are capable of self-reflection through the creation of diverse learning products.